Projected heroes and self-perceived manipulators: understanding the duplicitous identities of human traffickers - Mehlman-Orozco, Kimberly (Trends in organized crime, 2020)
This qualitative inquiry examines human trafficker identities through stories from convicted offenders. Thematic findings suggest that the projected-identity of sex traffickers may be different from their true self-identity. Identity regulation to produce the appropriate individual by situation facilitates both improvisational and patterned methods of victim recruitment. Sex traffickers exercise their coercive power predominately through the use of deception and fraud, projecting themselves as Bhonest heroes^ and Blovers^ of their victims. Rather than using force to perpetually repress victims, sex traffickers more frequently gain compliance by building a trauma bond with their victims, who are also typically found at the margins of society. Recruitment into a commercial sexually exploitive victimization involves the perceived fulfillment of physiological and emotional needs, as well as strategic infusion of counterculture virtues. For tenured sex traffickers, force is normally only intermittently exercised to punish recalcitrant victims in a way that maintains the longevity of control through trauma bonding.